Analysis of Measurement of the Quality of Using the Web-Based Computer Based Test (CBT) Application on User Satisfaction Using Servqual and CSI Methods at SMK PGRI 6 Denpasar - Triwayuni, I Gusti Ayu; Sudarma, Made; Alit Swamardika, Ida Bagus (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2025)
The web-based Computer Based Test (CBT) application is an innovation in the academic assessment system that replaces the conventional paper-based exam method. This study aims to analyze the quality of CBT application services on user satisfaction at SMK PGRI 6 Denpasar using the Servqual and Customer Satisfaction Index (CSI) approaches. The research sample consisted of 152 students in grades XI and XII. Data were obtained through online questionnaires and analyzed using the Servqual method to identify gaps between user expectations and perceptions, as well as CSI calculations to measure overall satisfaction levels. The results of the analysis show that 90% of indicators have negative gap values ??indicating that user expectations are higher than actual experiences. However, the CSI value of 82.64% is included in the very satisfied category, indicating that the CBT application still provides significant benefits. Therefore, feature development and service improvements are needed to meet user expectations more optimally.